SOTATERCEPT AS A POTENTIAL DISEASE-MODIFYING THERAPY IN PULMONARY ARTERIAL HYPERTENSION: A NARRATIVE REVIEW - Aleksandra Kamińska; Maria Miller; Aleksandra Pakulska; Aleksandra Błoch; Natalia Rządzińska (Archiv Euromedica, 2026)
Background Pulmonary arterial hypertension (PAH) is a progressive and potentially fatal disease characterized by increased pulmonary vascular resistance, pulmonary vascular remodeling, and right ventricular failure. To date, therapy has relied mainly on vasodilatory action and has not sufficiently improved patients' long-term prognosis. There is therefore a need for therapies targeting pathways involved in disease progression and pulmonary vascular remodeling. Aims To summarize current data on the mechanism of action, efficacy, safety profile, and therapeutic role of sotatercept in the treatment of PAH. Methods A literature review was conducted using the PubMed and Scopus databases. Publications concerning sotatercept and PAH were analyzed, with particular emphasis on clinical and preclinical studies, pooled analyses, systematic reviews, meta-analyses, and safety publications. Results Sotatercept is a first-in-class activin signaling inhibitor that acts on dysregulated pathways associated with pulmonary vascular remodeling. Preclinical studies have shown reductions in vascular remodeling, inflammation, and right ventricular dysfunction. In the PULSAR and STELLAR trials, the use of sotatercept in patients with PAH improved exercise capacity and hemodynamic parameters. In the STELLAR trial, sotatercept increased the six-minute walk distance by 40.8 m compared with placebo, and the risk of death or clinical worsening was reduced by 84%. Data from the SOTERIA study suggest that clinical benefits are maintained over longer follow-up. The most common adverse events included epistaxis, telangiectasia, and hematological abnormalities. Conclusions Sotatercept represents an important therapeutic innovation in the treatment of PAH as an add-on therapy that potentially affects the mechanisms of vascular remodeling. Further studies are needed to assess its long-term safety, impact on survival, and optimal place in treatment regimens.